Sensitivity Analysis through SWAT model for Sirsa River Basin in Western Himalaya - Verma, Narender; Dash, Pratik (National Geographical Journal of India, 2022)
In this paper an attempt has been made to perform sensitivity analysis of various hydrological variables through SWAT model for Sirsa river basin, an unguaged basin, in Western Himalayas. The study used remote sensing data derived evapo-transpiration(ET) to parameterize SWAT model through manual calibration. For this study twelve sub-basins using fifth order stream as threshold were delineated from Aster Dem. These were further subdivided into 179 HRUs by overlaying land use landcover(LULC), soil and slope layers. Climate input parameters were loaded to run the model for the period of 2001-2008, considering first three years as warm-up period. After initial SWAT run, sensitivity analysis was performed based on Latin LH-OAT method. From sensitivity analysis groundwater related parameters (GWQMN, REVAPMN, GW_REVAP and RCHR_DP), soil related parameters (SOL_Z, SOL_AWC and SOL_K) and HRU related parameters (EPCO, ESCO and CANMX) were found to be most sensitive.